SACRED PLACES AND HISTORICAL AND CULTURAL HERITAGE OF THE KYRGYZ (Based on the example of the Talas region) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article provides information about the historical and spiritual sites of the Kyrgyz people, including those revered as sacred in the Talas region. Shrines, mountains, stones, mausoleums, caves, trees, petroglyphs and tombs were of particular importance in the worldview of the Kyrgyz people. Each of them is closely connected with the spiritual beliefs, traditions and history of the Kyrgyz people, and today many of these sites are preserved as places of worship and pilgrimage. The respect of the Kyrgyz people for nature and the traditions of preserving shrines and objects will also be studied, and the importance of preserving this heritage will be emphasized. Their sanctity is also explained by their respect for the spirits of their ancestors and their connection with nature. In some places, these historical monuments have been preserved as shrines for religious ceremonies. Today, it is considered that this heritage has cultural and tourist significance and is protected as an important historical source reflecting the history, spiritual world and knowledge of the Kyrgyz people since ancient times. The article analyzes their spiritual significance and historical role.
Keywords: Holy places, tombs, pilgrimages, mausoleum of Manas Ata, springs, cultural heritage.